Ultrasound-Guided Quadrilateral Space Block for the Diagnosis of Quadrilateral Syndrome - Hamilton Chen; Vincent Reginald Narvaez (Case Reports in Orthopedics)
Quadrilateral space syndrome (QSS) is a rare nerve entrapment disorder that occurs when the axillary nerve and posterior circumflex humeral artery (PCHA) become compressed in the quadrilateral space. QSS presents as vague posterolateral shoulder pain that is exacerbated upon the abduction and external rotation of the shoulder. Diagnosis of QSS is difficult because of the vague presentation of QSS. In addition, even though MRI and MR angiography can be used in QSS diagnosis, there is currently no “gold standard” diagnostic imaging studies for QSS. In this case report, we describe a novel ultrasound-guided technique for a diagnostic quadrilateral space block and present a case where the diagnostic block was used to diagnose QSS. We believe that a diagnostic block of the quadrilateral space is a useful adjunct in the evaluation of patients with suspected QSS, especially in cases where examination findings and other diagnostic modalities are indeterminate.